Assessment of Bio-social Aspect with Cholelithiasis Patients in Baghdad City - shanon, Abd Al-Kareem; tawfiq, Narmeen (Iraqi National Journal of Nursing Specialties, 2006)
Objective: To find out the relationship between the bio-social aspect with cholelithiasis patients anddemographic characteristics in Baghdad city.Methodology: A purposive (non-probability) sample of (100) patients, from (20-70) years old, who wereselected from patients who were admitted to hospital at preoperative stage, from Gastroenterology andHepatology Hospital, Baghdad Teaching Hospital, Al-Yarmook Teaching Hospital, Al-Karama TeachingHospital, Teaching Hospital. A descriptive study was carried out from 25th of June 2004 to the end of October2004.An assessment form was constructed for the purpose of the study. Test-retest reliability was employed throughcomputation of Pearson correlation coefficient. Content validity of the assessment form was determined througha panel of experts. Data were collected with interview technique.Data were analyzed through descriptive statistical approach (frequency and percentage) and inferentialstatistical approach (chi-square and correlation coefficient).Results: The study indicated that the mean of age was (52.6) year. The majority of them were females who fair;multiparty lived in urban, obesity, illiterate, low socio-economic status.The result of the study confirmed that the bio-social aspect had an effect on the incidence of cholelithiasis.Recommendations: The study recommended that the number of Gastroenterology and Hepatology Hospitalshould be increased in Iraq because; some of the patients come to Baghdad to treatment.Patients with positive family history for cholelithiasis must be educated and informed about [diet and fluid,which are related to gallstones, exercise, Regular follow-up include, (routine X-ray, ultra-sound generallaboratory investigations), drugs use and side effect].